The Image of Javanese Women in Gadis Pantai Novel by Pramodeya Ananta Toer; Social Realism Review (Universitas Negeri Semarang, 2019)
The image of Javanese women become an interesting review matter in a novel study. The image can be seen in Gadis Pantai novel by Pramoedya Ananta Toer in which is full of cultural values and social stratum classes. The focus of this research is the image of Javanese women in the novel by using social realism review. The method was hermeneutic by reading repetition in the novel, allowing the reader to deconstruct structurally to reveal the meaning inside of the novel. The data source is the excerpts of the novel in the form of statement, written words, and the actions of the characters in the novel. The data collection techniques were literature study, observation, and notes. The data analysis technique was content analysis. The findings are: (1) the image of Javanese women in the novel could be found on Gadis Pantai character, maid, mother, and Mardinah. The image of Javanese women in the novel showed nglaras rasa and angon rasa, welas asih, nrima and rasa rumangsa, kanthong bolong and gangsir ngenthir, kridha grahita, ngelmu begja, the feeling to have and jealousy, fear, and humble, and (2) the representations of Javanese woman image in the novel could be seen from social aspect, covering from ethics toward people, higher social stratum person, and society inside.